Nonvanishing at spatial extremity solutions of the defocusing nonlinear Schrödinger equation. (27th September 2018) - Gialelis, Nikolaos; Stratis, Ioannis G.
Abstract : We show local existence of certain type of solutions for the Cauchy problem of the defocusing nonlinear Schrödinger equation with pure power nonlinearity, in various cases of open sets, unbounded or bounded. These solutions do not vanish at the boundary or at infinity. We also show, in certain cases, that these solutions are unique and global.